Usulan Perancangan Tata Letak Gudang dengan Menggunakan Metode Class Based Storage - Aryansah, Nicky Fenky; Murnawan , Hery (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
CV. Bandung Central Arteri Samudra is a manufacturing industry engaged in the distribution of fishing equipment located on Jalan Kembang Jepun no. 194 – 196, ex. Nyamplungan subdistrict of Pabean Cantikan Surabaya. This research examines the warehouse layout using the